Carotid intima media thickness, neutrophil to lymphocyte ratio, and platelet to lymphocyte ratio in multiple sclerosis - Negin Eissazade; Elyar Alizadeh Najmi; Dina Hemmati; Maryam Mehdizadeh; Zahra Mirzaasgari (Scientific Reports)
Abstract Evidence on carotid intima-media thickness (cIMT), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) in patients with multiple sclerosis (MS) is limited. We aimed to assess cIMT, NLR, and PLR levels, and their potential associations in patients with MS. This case–control study included 110 patients with MS and 110 healthy controls. All participants underwent comprehensive history taking, as well as general and neurological examinations. Disability was assessed using the Expanded Disability Status Scale (EDSS). cIMT was measured by B-mode ultrasound, 10 mm before the bifurcation of the common carotid artery. Compared to healthy controls, patients with MS demonstrated significantly elevated NLR, PLR, and cIMT values, even after adjustment for age, gender, and BMI (P < 0.001). Within the MS group, higher cIMT values were significantly associated with secondary progressive MS type (P = 0.003) and correlated with higher EDSS scores (P < 0.001); however, these findings lost statistical significance after controlling for age, gender, and BMI. NLR and PLR demonstrated acceptable diagnostic accuracy for MS, while mean cIMT showed excellent discriminative ability. All three markers—NLR, PLR, and mean cIMT—exhibited acceptable performance in assessing disease severity. MS is associated with significantly elevated levels of NLR, PLR, and cIMT. While cIMT was not associated with NLR or PLR, it may serve as a valuable, non-invasive tool for evaluating vascular involvement and disease progression in MS. Further multi-center studies with larger cohorts are warranted to confirm these findings